(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: PTEN (phosphatase and tensin homolog) gene is located at the 10q23 region that regulates cell proliferation and survival mainly by regulating PI3K (phosphatidylinositol 3-kinase)-AKT (protein kinase B) signaling pathways. PTEN gene is one of the most frequently mutated tumor suppressor genes in human cancer. Loss of PTEN gene can cause overgrowth, proliferation, survival, and metabolism of tumor cells. In breast cancer, loss of PTEN gene is associated with the occurrence of tumor and is significantly correlated with its characteristics. Objective: To assess the frequency of PTEN deletion or signal reduction in breast cancer in a sample of Iraqi female patients using FISH technique and its relation with clinico-pathological parameters (age, tumor size, multicentricity, histopathological types, grade, pathological stage and lymph node status). Methods: This is a retrograde, case control study, which was conducted at the Department of Pathology and Forensic Medicine, College of Medicine, Al-Nahrain University for the period between October 2019 to November 2020. It involved 30 patients with breast cancer who underwent mastectomy and 30 patients with benign breast lesions. Results: PTEN gene deletion or signal reduction was observed in 8 (26.67%) out 30 breast cancer patients. There was a significant relation between PTEN gene deletion (or signal reduction) and larger tumor size, higher grade, advanced pathological stage, and metastasis to more than 4 lymph nodes. Conclusion: There was significance difference between cases and control groups regarding PTEN deletion or signal reduction. There was significant correlation between PTEN gene deletion or signal reduction and larger tumor size, higher pathological grade and advanced stage. Keywords: PTEN gene, breast cancer, FISH technique Citation: Al-Taie MRF, Qasim BJ. Assessment of PTEN deletion or signal reduction in breast carcinoma using FISH technique in a sample of Iraqi female patients. Iraqi JMS. 2021; 19(2): 152-162. doi: 10.22578/IJMS.19.2.4